Dari STOVIA ke Salemba: Sekolah Dokter Jawa Cikal Bakal Fakultas Kedokteran Universitas Indonesia - Ilham Arsandi Firmansyah; Jumardi (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2021)
Local history is an interesting theme to look at in historical research. Then in the purpose of this research will discuss the local history of the School of Javanese Doctors became the forerunner of the establishment of the Faculty of Medicine, University of Indonesia located in Salemba. In this method use historiography methods such as topic selection stages, heuristics, achievements, to historiography or writing. The results of this study as to provide information about the School of Javanese Doctors who forerunner became the Faculty of Medicine, University of Indonesia located in Salemba No. 6. Therefore, the existence of the Faculty of Medicine Building, University of Indonesia which is still standing until now is a silent witness to the existence of a medical school in Jakarta.